Molecular Identification of Endospore-Forming Rhizobacteria from Organic Cabbage Farm Potential as Biocontrol against Phytopathogen Xanthomonas campestris (Indonesian Society for microbiology, 2016)
Rhizobacteria are rhizosphere competent bacteria that colonize and proliferate in all the ecological niches found on the plant roots at all stages of plant growth, in the presence of a competing microflora. These bacteria are potential as biological control Â agent to inhibit the growth of phytopathogen. The aim of this study was to isolate endospore-forming rhizobacteria from cabbage farm and determine its ability as biocontrol against Xanthomonas campestri, a pathogen causing black rot on cabbage. The methods used consisted of isolation, antibacterial activity test, biochemical characterization and molecular identification. Fourteen isolates of endospore-forming rhizobacteria were obtained from cabbage farming. Isolate K.9 had the highest ability to inhibit the growth of X. campestri. Based on molecular characterization by sequence analyses of 16S rRNA, isolate K9 had 97% homology with Bacillus cereus strains BF15.